An EEG Voyage in Search of Triphasic Waves—The Sirens and Corsairs on the Encephalopathy/EEG Horizon: A Survey of Triphasic Waves. Issue 5 (September 2021) - Kaplan, Peter W.; Gélisse, Philippe; Sutter, Raoul
Abstract : Summary: Generalized periodic discharges with triphasic wave (TW) morphology, long referred to as TWs, are typical of many toxic, metabolic, infectious, and cerebral structural problems, often in concert. Identifying TWs has been challenging for the electroencephalographer and clinician, as has been their cause, significance, prognosis, and treatment. This review highlights the many different patterns of TWs with commentary on their various causes and etiologies, characteristics, different morbidities, differentiation from nonconvulsive status epilepticus, and their prognosis. The articles in this Journal of Clinical Neurophysiology special issue on TWs will review the many challenges the clinician face when TWs are sighted.